Ammon in Transition from Vassal Kingdom to Babylonian Province - Lipschits, Oded (Bulletin of ASOR, 2004)
This article discusses the archaeological data from Ammon during the seventh-fifth centuries B.C.E., while considering the broader historical picture of the Babylonian period and comparing it with the historical, demographical, and geopolitical processes that occurred during this period in Judah. I will claim that Ammon was subjugated by the Babylonians in 604 B.C.E. and became a vassal kingdom. During the Babylonian expedition of 582/581 B.C.E., the invading army destroyed the fortified cities near the kingdom's northwestern border and on the main road to the capital and might also have hit Rabbat-Ammon. The outcome of this expedition was that Ammon became a province of the Babylonian Empire. As part of their methods of ruling and exploiting the hilly conquered territories in Hatti-Land, the Babylonians established a new capital (Tall al-ʿUmayri), at a site not far from the ancient capital of Rabbat-Ammon, allowing the continued existence of the rural settlement in the area around it. The ʿUmayri-Hisbān region specialized in wine and oil production, used mainly for paying taxes.